Non-Tariff Barriers and Factors that influence The Indonesian Cocoa Export to Europe - Raditya Anggoro; Widyastutik Widyastutik (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2016)
The aim of this study are: first, to analyse the competitiveness of Indonesian cocoa in the European Unio market; second, to analyse the competitiveness and the factors that influence the Indonesian cocoa exports to the EU market; third, to calculate the non-tariff barriers imposed by the European Union market for Indonesian cocoa. Methods used are the RCA index and gravity models. The differences between actual and potential trade flows are indicated as non-tariff barriers. Results of the calculation RCA is showed that all destinations of a cocoa export have a high competitiveness (RCA> 1) but tend to decrease. Results of the estimate gravity models show the factors influencing the Indonesian cocoa exports are the real per capita GDP of Indonesia and the destination country, CPI of destination countries, the economic distance, exchange rates, and tariff. The result of non-tariff barriers indicated that the Netherlands is the state which has the largest non-tariff barriers among the most other EU countriesDOI: 10.15408/sjie.v5i1.3131